A simple and effective model for prediction of effective thermal conductivity of vacuum insulation panels. Issue 1 (21st August 2015) - Kan, Ankang; Kang, Liyun; Wang, Chong; Cao, Dan
Abstract: The excellent thermal insulation performance of vacuum insulation panels (VIPs) make them widely applied in energy conservation fields, especially in buildings engineering. This research work proposes a simple, yet extremely effective, alternative model for prediction of the effective thermal conductivity (ETC.) of VIPs. The ETC. of VIPs is function of the thermal conductivity of the core materials, the equivalent thermal conductivity of the rarefied gas embraced in the core and the equivalent thermal conductivity of radiation in the early studies. The micro structure of the porous core materials and vacuum degree are taken into consideration and the prediction numerical model for the ECT of VIPs is developed. The relationship of the vacuum degree versus the ETC. is theoretical analyzed. Three types VIPs are made from the polyurethane foam materials, superfine fibrous materials and nano-granular silica materials as the core materials. For each type, the vacuum degree and the thermal conductivity are collected, including the comparison between the testing results and the prediction model. The agreement between the model and the experimental results is fairly well when the air pressure is very low. The vacuum maintaining and service life of the VIPs are also discussed. The research work is meaningful for the enhancement of stability and the development of vacuum insulation panels.